Penerapan Model Pembelajaran PAIKEM untuk Meningkatkan Hasil Belajar pada Pembelajaran IPA - Siswanto Siswanto; Ramdhan Witarsa; Nurmalina Nurmalina (Departement of Mathematics Education, 2022)
The purpose of this study was to explain the steps for implementing the PAIKEM learning model with the Demonstration method to improve student learning outcomes in class IV C SD Negeri 024 Tambusai. This study uses a qualitative and quantitative approach to the form of research in the form of classroom action research. This research was conducted in two cycles and each cycle consisted of two meetings. This research took place at SD Negeri 024 Tambusai with research subjects being students of class IV C. Data collection in this study used observation, documentation and test techniques. Data were analyzed using quantitative data analysis based on the SD Negeri 024 Tambusai curriculum with 67 individual Minimum Completeness Criteria (KKM) and classical completeness that Sudiyono had suggested was 75%. The increase in student learning outcomes on the material properties of sound in class IV C SD Negeri 024 Tambusai in each cycle can be seen from the results of the first cycle test, the average value is 66.7 with a 60% classical completeness percentage, to 81.8 with a completeness percentage classical 92% in cycle II. So, the application of the PAIKEM learning model to material properties of sound can improve student learning outcomes in class IV C